Surat Al-Layl: An Analytical Study (Abhat Journal, 2023)
The research deals with the interpretation of Surat Al-Layl as an analytical study, in which it shows the definition of the holy Surah briefly, its merits, its relevance to the surahs before and after it, its verses focus and the most prominent topics; Then it interprets its verses in terms of words and structures, shows the rhetorical subtleties and linguistic spots contained therein.      The surah shows the pursuit of the servants is different and reveals the reasons of facilitation for ease and hardship, invites to purify the soul by obedience, and intimidates to not to dirt by disobedience, through explain the penalty resulting from the recommendation and its opposite.
Keywords: Analysis; Interpretation; Verse Indication; Surat Al-Layl; Subtleties